Genomics‐assisted breeding for successful development of multiple‐stress‐tolerant, climate‐smart rice for southern and southeastern Asia. Issue 1 (12th January 2021) - Yadav, Shailesh; Sandhu, Nitika; Dixit, Shalabh; Singh, Vikas Kumar; Catolos, Margaret; Mazumder, Ratna Rani; Rahman, Mohammad Akhlasur; Kumar, Arvind
Abstract: Rice ( Oryza sativa L.) in rainfed marginal environments is prone to multiple abiotic and biotic stresses, which can occur in combination in a single cropping season and adversely affect rice growth and yield. The present study was undertaken to develop high‐yielding, climate‐resilient rice that can provide tolerance to multiple biotic and abiotic stresses. An assembled first‐crossing scheme was employed to transfer 15 quantitative trait loci (QTL) and genes— qDTY1.1, qDTY2.1, qDTY3.1, qDTY12.1 (drought), Sub1 (submergence), Gm4 (gall midge), Pi9, Pita2 (blast), Bph3, Bph17 (brown plant hoppers), Xa4, xa5, xa13, Xa21, and Xa23 (bacterial leaf blight)—from eight different parents using genomics‐assisted breeding. A funnel mating design was employed to assemble all the targeted QTL and genes into a high‐yielding breeding line IR 91648‐B‐1‐B‐3‐1. Gene‐based linked markers were used in each generation from intercrossing to the F6 generation for tracking the presence of desirable alleles of targeted QTL and genes. Single‐plant selections were performed from F2 onwards to select desirable recombinants possessing alleles of interest with suitable phenotypes. Phenotyping of 95 homozygous F6 lines carrying six to 10 QTL and genes was performed for nonstress, reproductive‐stage (RS) drought, blast, bacterial leaf blight (BLB), gall midge (GM), and for grain quality parameters such as chalkiness, amylose content (AC), gelatinization temperature (GT), and head rice recovery (HRR). Finally, 56 F7 homozygous lines were found promising for multiple‐location evaluation for grain yield (GY) and other traits. These multiple‐stress‐tolerant lines with the desired grain quality profiling can be targeted for varietal release in southern and southeastern Asia through national release systems. Core Ideas: Genomics‐assisted breeding used to assemble multiple genes and QTL for high‐yielding breeding line. High‐yielding, climate‐resilient, superior quality rice lines with 6–10 genes and QTL for various stresses. New lines used as donor parent to introgress multiple genes and QTL in other genetic backgrounds.